Artistic literature and its role in the natiogenesis: the main vectors of the research of the department of foreign literature in 2021–2025 - Butyrchyk, Hanna M. (Journal of the Belarusian State University. Philology, 2024)
The main vectors of the research work at the department of foreign literature of the faculty of philology of the Belarusian State University are considered. Based on the theories of Bhabha (nation as narration), Anderson (nation as an imagined community), Hübner (nation as an mythical substance), Hobsbawm (invention of tradition), Toynbee (narrative history) and taking into consideration the main approaches of Herman, Brokmeier, Kharre to narrative in literary studies the definition of national narrative was suggested. The vectors of the multidimensional analysis of national narrative through fiction were delineated. The specific role of context was designated.
Keywords: Belarusian literature; foreign literature; context; national narrative; mythologisation; discourse practices; comparative studies; literary criticism; department of foreign literature